O papel da religiosidade/espiritualidade no cuidado de adolescentes com Transtorno Depressivo Maior: uma revisão a partir da produção bibliográfica da psicologia da religião no Brasil - Santos, Gilberto Diniz dos (2023)
For a long time, it was assumed that major depressive disorder did not occur or did not exist in adolescence. However, we currently know that at this stage of life, this disorder is very common to occur, being a highly serious problem, as it can accompany suicidal ideation and suicide itself among adolescents. In this sense, several studies have discussed the importance of Religiosity and Spirituality in adolescence as a resource for coping with challenges related to mental health. The present research sought to carry out a survey of the national production, from the psychology of religion, on the role of Religiosity/Spirituality in the care of adolescents with Major Depressive Disorder, identifying the most frequent themes in the area and highlighting the characteristics of the main topics in this research, from a cognitive-behavioral approach. The main finding of this research is an understanding of actions that are beneficial or harmful to the mental health of adolescents with Major Depressive Disorder and some practices that should be considered in order to understand the role of religiosity/spirituality. R/S can be used as a tool to deal with difficult life situations and can lead to improve mental health. We conclude by acknowledging the importance of religiosity and with recommendations for future research based on Brazilian literature